The cell origins of foam cell and lipid metabolism regulated by mechanical stress in atherosclerosis - Ouyang, Zhi; Zhong, Jian; Shen, Junyi; Zeng, Ye (Frontiers in Physiology, 2023)
Atherosclerosis is an inflammatory disease initiated by endothelial activation, in which lipoprotein, cholesterol, extracellular matrix and various types of immune and non-immune cells are accumulated and formed into plaques on the arterial wall suffering from disturbed flow, characterized by low and oscillating shear stress. Foam cells are major cellular component in atherosclerotic plaques, which play an indispensable role in the occurrence, development and rupture of atherosclerotic plaques. It was previously believed that foam cells were derived from macrophages or smooth muscle cells, but recent studies have suggested that there is other sources of foam cells. Many studies have found that the distribution of atherosclerotic plaques is not random but distributed at the bend and bifurcation of the arterial tree. The development and rupture of atherosclerotic plaque are affected by mechanical stress. In this review, we reviewed the advances in foam cell formation in atherosclerosis and the regulation of atherosclerotic plaque and lipid metabolism by mechanical forces. These findings provide new cue to investigating the mechanism of occurrence and progression of atherosclerotic plaques.